Evaluasi Pembelajaran di Pondok Pesantren - Faisal, Ahmad (PT The Collaboration UVW, 2023)
Islamic boarding schools are educational institutions that specialize in deepening religious knowledge, especially traditional Islamic boarding schools still require a study of the learning system and the scope of teaching materials, because there are no curriculum standards and quality control, then how about the implementation of learning evaluation in Islamic boarding schools seen from planning, implementation, monitoring and data processing of learning evaluation results, research methods used in this study is a qualitative research with data collection techniques of observation, documentation and interviews as well as qualitative descriptive data analysis with inductive conclusions. the limitations of the material to be tested as in the Riyadussholihin hadith book from pages 1-25, the second implementation of learning evaluation in Islamic boarding schools uses more test evaluation instruments, namely oral tests and written tests, third monitoring in Islamic boarding schools when carrying out evaluations such as nisfu sanah exams and exams the final sanah monitors or supervises the implementation of the exam and the fourth data processing of the results of the evaluation of learning in Islamic boarding schools after the implementation of the learning evaluation makes corrections and provides scores and scores with a value range of 1-10 for answers n of the students are then reported in the form of student report cards.